Heteroplasmy due to coexistence of mtCOI haplotypes from different lineages of the Thrips tabaci cryptic species group. Issue 4 (31st January 2017) - Gawande, S.J.; Anandhan, S.; Ingle, A.A.; Jacobson, Alana; Asokan, R.
Abstract: Heteroplasmy is the existence of multiple mitochondrial DNA haplotypes within the cell. Although the number of reports of heteroplasmy is increasing for arthropods, the occurrence, number of variants, and origins are not well studied. In this research, the occurrence of heteroplasmy was investigated in Thrips tabaci, a putative species complex whose lineages can be distinguished by their mitochondrial DNA haplotypes. The results from this study showed that heteroplasmy was due to the occurrence of mitochondrial cytochrome oxydase I (mtCOI) haplotypes from two different T. tabaci lineages. An assay using flow cytometry and quantitative real-time PCR was then used to quantify the per cell copy number of the two mtCOI haplotypes present in individuals exhibiting heteroplasmy from nine geographically distant populations in India. All of the T. tabaci individuals in this study were found to exhibit heteroplasmy, and in every individual the per cell copy number of mtCOI from lineage 3 comprised 75–98% of the haplotypes detected and was variable among individuals tested. There was no evidence to suggest that the presense of lineage-specific haplotypes was due to nuclear introgression; however, further studies are needed to investigate nuclear introgression and paternal leakage during rare interbreeding between individuals from lineages 2 and 3.